The comparative study on financial performance between Citibank Berhad and Standard Chartered Bank Malaysia Berhad / Che Muhamad Azli Che Ab Hadi - Che Ab Hadi, Che Muhamad Azli (Faculty of Business and Management, 2010)
This case study was conducted to evaluate the financial performance of both International banks that are operating in Malaysia, Citibank Berhad and Standard Chartered Bank Malaysia Berhad which come from a same banking sector. But, there is a different from their operation in running the business. For completion of this report, secondary data and other approaches such as common sizing, financial ratios and gap analysis has been use as a data collection. The data is taken from external sources such as journal, internet, and newspaper. The study examines four type of ratios include (1) common size, (2) liquidity, (3) capital structure and solvency, (4) Return on Investment